(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2025)
The cultural heritage of the peoples of Central Asia has been shaped by ancient beliefs and customs closely connected with nature. Such rituals were intended to maintain harmony between humans and the natural environment, emphasizing values such as fertility, prosperity, health, and peace. Among the most significant nature-related ceremonies are the celebration of “Navruz,” rain-invoking rituals, the preparation of “Sumalak,” and practices of worshiping water, plants, and the sun. Comparative analysis reveals both common and distinct features among the nations: water rituals among Uzbeks, wind-related traditions among Kazakhs, and plant or sun worship among Tajiks. These rituals serve as symbols of national identity, help form ecological awareness, and preserve cultural continuity. The article explores the historical origins, modern transformation, and ecological-cultural significance of these nature-related rituals in Central Asian societies